(untitled) (مجلة الواحات للبحوث والدراسات, 2016)
The purpose of this paper is to test the effect of foreign direct investment (FDI) on economic growth in North African countries using the recent growth theory and econometrics technique; theoretically the most of the recent economic research consider the foreign direct investment one of the important factors of growth in many region,I examined the hypothesis on north African countries and the results showed that the FDI inflows impact on economic growth in North African countries statistically has a positive effecteven thoughFDI inflows to the region still doesn’t achieve the desired result. Key words: Economic Growth; foreign Direct Investment (FDI); North African countries